Resistant Starch Type 5 in Buras as Indonesian Traditional Food: Influence of Amylose Content and Multiple Cooling-Reheating Cycles - Sabrina, A'isyah Mutiara; Pranoto, Yudi; Marseno, Djagal Wiseso; Prawira, Muhammad Aditya (Department of Technology of Agricultural product (THP) Jambi University, 2025)
High-resistant starch foods are gaining attention for their potential to lower the risk of diabetes, obesity, and degenerative diseases. One type of resistant starch (RS) is RS5, a starch-lipid complex. This study investigated the effects of amylose content and physical modifications on Buras, a traditional Indonesian food made from rice and coconut milk. The physicochemical characteristics were evaluated using three rice varieties (Setra Ramos, C4 Super, and Rojo Lele) and cooling-reheating cycles (Control, 1 cycle, 2 cycles). Setra Ramos exhibits the highest amylose and RS5 contents at 25.14% and 26.54%, respectively. High amylose content facilitates the formation of lipid-amylose helical structures, inhibiting starch digestibility by enzymes such as α-amylase. RS5 in Buras was identified by the presence of amylose-lipid complexes, as indicated by Scanning Electron Microscopy (SEM) for visualization of granule structure, X-ray Diffraction (XRD) for crystallinity, and Fourier-transform infrared spectroscopy (FTIR) for functional groups. The best treatment was obtained at 1 cycle of cooling-reheating (S1), which increased RS by 9% and reduced starch hydrolysis by 11%. This study examined strategies to enhance RS5 content and reduce starch digestibility with physical modifications. The findings showed that cooling-reheating cycle treatment significantly (p<0.05) increased RS content in Buras. This increase correlated with increased starch retrogradation and the formation of amylose-lipid complexes, thereby reducing starch digestibility. Consequently, traditional food products become healthier and help control blood sugar levels. Therefore, simple thermal modification, such as cooling and reheating, improves the functional properties of starch-based traditional foods.